2012
DOI: 10.1073/pnas.1203451109
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer-based combination therapy of cisplatin with tetramethyl- p -phenylenediamine for ovarian, cervical, and lung cancers

Abstract: The platinum-based chemotherapy is the standard treatment for several types of cancer. However, cancer cells often become refractory with time and most patients with serious cancers die of drug resistance. Recently, we have discovered a unique dissociative electron-transfer mechanism of action of cisplatin, the first and most widely used platinum-based anticancer drug. Here, we show that the combination of cisplatin with an exemplary biological electron donor, N,N,N′,N′-tetramethyl-p-phenylenediamine (TMPD), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 50 publications
2
50
0
1
Order By: Relevance
“…Chemotherapy is among the pilot methods of treatment for cancer patients (Florea and Büsselberg 2011;Luo et al 2012;Raschi and De Ponti 2012). Several investigators have reported that anticancer agents have been utilized for the chemotherapy of various cancers such as sarcoma small cell lung cancer, ovarian cancer, lymphomas, germ cell tumors, and CNS disability (Iwata et al 2012;Lee et al 2012a, b;Rinne et al 2012), but they have also been implicated in causing various kinds of toxicity after treatment in cancer patients measured as adverse effects (Dharap et al 2005;Erkurt et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Chemotherapy is among the pilot methods of treatment for cancer patients (Florea and Büsselberg 2011;Luo et al 2012;Raschi and De Ponti 2012). Several investigators have reported that anticancer agents have been utilized for the chemotherapy of various cancers such as sarcoma small cell lung cancer, ovarian cancer, lymphomas, germ cell tumors, and CNS disability (Iwata et al 2012;Lee et al 2012a, b;Rinne et al 2012), but they have also been implicated in causing various kinds of toxicity after treatment in cancer patients measured as adverse effects (Dharap et al 2005;Erkurt et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…2 and Supplementary Fig. S1, we further measured DNA DSBs in cancer cells treated by FMD-2Br-DAB in combination with IR (225 kV X-rays), using the HCS DNA Damage (gH2AX) Kit (24)(25)(26). Figure 3 shows the fluorescence images of cervical cancer (ME-180) cells with/without the treatment of 25/200 mmol/L FMD and the yield of DNA DSBs detected by gH2AX foci with various X-ray doses, respectively.…”
Section: In Vitro Dna Dsb Measurements In Cancer Cellsmentioning
confidence: 99%
“…At 12 hours after X-ray irradiation, the cells were fixed and stained. Following the detailed protocol provided by the manufacturer, we performed the HCS DNA Damage Assay of the treated cells, as described previously (24)(25)(26). The images of cells were acquired with a Nikon Eclipse TS100 fluorescence microscope; quantitative analyses of activated gH2AX (DNA DBS yield) in the cells were performed using an Image J software.…”
Section: In Vitro Dna Dsb Assaymentioning
confidence: 99%
See 2 more Smart Citations